2019
DOI: 10.2109/jcersj2.18180
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the deterioration law and mechanism of aeolian-sand powder concrete in the coupling environments of freeze-thaw and carbonization

Abstract: In this study, aeolian-sand powder was used for replacing cement-based gelling material in order to prepare aeolian-sand powder concrete in C25 and C35 strength grades. Through relative dynamic elastic modulus and carbonization depth changes, the deterioration laws of the aeolian-sand powder concrete under the coupling effects of freeze-thaw + carbonization and carbonization + freeze-thaw were studied. Then, field emission scanning electron microscopy, X-ray diffraction, and nuclear magnetic resonance porosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The unconfined compressive strengths of TRA-7d and TRA-28d samples reached 2878 and 3421 kPa, respectively, which were 26.1% and 20.5% higher than those having recycled aggregate content of 10%. It can be found through the analysis that the recycled aggregate content has a great influence on the unconfined compressive strength of samples, which is also consistent with the research results obtained by Li Yugen, Li Fang et al [24,25]. There are a large number of clay particles in soft soil.…”
Section: Peak Strengthsupporting
confidence: 87%
“…The unconfined compressive strengths of TRA-7d and TRA-28d samples reached 2878 and 3421 kPa, respectively, which were 26.1% and 20.5% higher than those having recycled aggregate content of 10%. It can be found through the analysis that the recycled aggregate content has a great influence on the unconfined compressive strength of samples, which is also consistent with the research results obtained by Li Yugen, Li Fang et al [24,25]. There are a large number of clay particles in soft soil.…”
Section: Peak Strengthsupporting
confidence: 87%
“…Additionally, the chemical reaction between the C-S-H gel and Ca(OH) 2 and CO 2 within the specimens produces a substantial amount of CaCO 3 , filling the defective areas between the ITZ. This improves the pore structure and optimizes the structure of the ITZ, thereby enhancing the compressive strength of the concrete specimens [31][32][33].…”
Section: Effect Of Carbonization On the Compressive Strengthmentioning
confidence: 99%
“…15, x FOR PEER REVIEW the ITZ. This improves the pore structure and optimizes the structure of the IT enhancing the compressive strength of the concrete specimens[31][32][33].…”
mentioning
confidence: 99%
“…The research by Dong et al [33] demonstrated that the inclusion of AS in concrete causes changes in the arrangement of hydration product particles, resulting in a dual effect on the frost resistance of concrete. The F-T damage mechanism has been studied by Li [34] and Bai et al [35] using SEM, and their results indicate that increasing the AS proportion in concrete can enhance its frost resistance.…”
Section: Introductionmentioning
confidence: 99%